Quo Vadis the Common Agricultural Policy amid Tomorrow’s Challenges? - ANDREEA - EMANUELA DRĂGOI (Global Economic Observer)
Under the current economic environment, shaped by the widespread consequences of the war in Ukraine, the European Union’s agricultural sector and its rural development policy are facing numerous challenges with significant impact on agricultural production, food security and the welfare of the European farmers. This research paper aims to investigate the Common Agricultural Policy’s (CAP) response to those challenges in the current financial framework (2023-2027) using a comparative analysis based on the published CAP Strategic Plans (CSP) of the Member States. To this purpose our methodological approach will use a series of indicators selected for highlighting the measures proposed in various Member States to increase food security, to boost sustainable agricultural production and to protect the farmers’ income. Our main objective is to illustrate the future of CAP funding using as case study Romania’s approved CSP, while presenting the specific measures proposed in this country to support its agricultural sector among the challenges brought for its farmers by the current economic international context.